Pentingnya Pendidik dalam Penerapan Teknologi Menghadapi Era Society 5.0 yang Berimplementasi Akhlaq pada Anak Marjinal - Muttaqin, Dafiq Nur; Salsabila, Unik Hanifah; Praditya, Alfathera Bima (Lembaga Yasin AlSys, 2022)
Writing this article aims to provide an explanation regarding the background of the importance of education in the application of technology to face the era of Societ 5.0 which implements morals in marginalized children. The role of technology on the morals of marginalized communities where the subjects are marginalized children who have various backgrounds. Marginal children are some of the children who are teenagers to adults where they live freely without any strict assistance from their parents, it is not surprising that we often see many punk children on the edge of the highway. Punk children are also part of marginalized children. Whoever and wherever the children are, they all still need education. Education which they can get from non-formal institutions. Because they also know the position they live in today where they know that life is in an era that continues to grow and is getting louder and louder. However, their enthusiasm in seeking knowledge and identity in life is not vulnerable. We can know that not all marginal children are naughty but there are still many marginal children who are moral and still want to learn a lot of knowledge, especially religious knowledge. They also often apply alkhlaq in their daily life, although most likely most of them look scary and scary. Regarding the information that we have obtained, we use data collection obtained through observation in which marginalized communities also have the right to be good so that in the future marginal communities will be able to be in their environment and be able to convey the goodness they have received and the development of the era of society 5.0. can adapt well.